A Case Study of Solid Waste Management Practices of Hetauda Sub Metropolitan City: Situations, Prosperities, and Challenges - Sah Kanu, Birendra Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
The study revealed that women played major role in waste production. The main reason behind this can be the patriarchal thinking of society. Women are more involved in household works by their nature. The migration rate is rapidly increasing since last 5 years. The 40 percent of people migrated in this municipality within last 10 years which has directly influenced on the quantity of wastes. The majority of the houses in this municipality are non-concrete and semi-concrete. One third of houses are tiled, tin roofed or thatched roofed. All these structures highlight the condition of municipality. But most of these houses composed of developed, modern and trench toilet. Now, the dwellers of Hetauda have access to every kind of modern technologies. The most accessible technology is mobile. The use of coal, wooden dust, and firewood is also in the same ratio of cooking gas which verified the town is still in the stage of semi[1]urbanization. The lack of governmental or municipality level policy, and lack of institutional accountability has created more problem in waste management. The lack of separate act on waste management has created challenge to waste management system.